ACCELERATE NON-ENGLISH LECTURERS’ MASTERY OF ENGLISH THROUGH CONTENT-BASED INSTRUCTION - Asna Usman Dilo; Sri Dewi Jayanti Biahimo (ETERNAL (English, Teaching, Learning and Research Journal), 2019)
The articles aims of discussing about using content based approach in accelerating non-English lecturers’ mastery of English. Out of three main types of Content-Based Instruction, this study uses the theme-based language instruction to accelerate the non-English lecturers’ mastery of English. Therefore, the question was asked; can the content based approach accelerate the non-English lecturers’ mastery of English.  This study was an action research study, where pre-test and posttest were administered to obtain the data, in addition to observation and literature study. The study is conducted in two cycles; each cycle consists of 5 meetings. The indicator of the study is that the study is completed when 75% of the lecturers were able to reach at least 75 points in the test. The pretest reveals that the average lecturers’ score is 63.50 and following the treatment using this approach at the end of the second cycle, the average lecturers’ mastery is 80.2%. Therefore, it is concluded that content-based instruction can accelerate the non-English lecturers’ mastery of English.